Longitudinal modes competition in a micro ring laser subject to both a self and a cross optical feedback - Khoder, Mulham (Communications in nonlinear science & numerical simulation, 2018)
•The competition between the modes enhanced by the two feedback controls the emission.•The effect of the parameters of the two feedback on the ring laser has been investigated.•Undesirable effects of one feedback can be minimized using a second compact feedback. External Optical feedback can severely change the stability and the performance of semiconductor ring lasers. To reduce the undesired effect of the optical feedback, we propose to use a second feedback to stabilize the wavelength and the intensity of the ring laser even in the presence of undesired external reflections. In this work, we numerically investigate the dynamical behavior of the semiconductor ring laser when it is subject to two optical feedback simultaneously using a two-directional mode rate equation model. The results show that the laser’s output is determined according to the competition between the longitudinal modes which are enhanced by the different feedback. The undesired changes of the dynamical behavior of the laser due to the effect of the one feedback can be minimized using a second controlled feedback. The second feedback has been chosen with a short delay line so it can be integrated on the same chip with the laser. This approach allows to avoid the complex integration process of magneto-optic materials which are normally required for on-chip isolation. The fabrication of the delay line and the control of the strength and the phase of the proposed feedback are currently supported and offered using standard building blocks by several integrated optics foundries.